(untitled) (Contemporary Journal of Social Science Review, 2025)
This study examines the discourses surrounding Muslim women’s veiling, analyzing both global media narratives and local Pakistani texts using Critical Discourse Analysis (CDA). The veil, encompassing hijab, niqab, and burqa, is a site of contestation where gender, religion, and identity intersect. Global discourses often frame veiling as oppression or cultural backwardness, while local narratives emphasize piety, moral agency, and religious obligation. Using Fairclough’s CDA framework, this paper investigates how language, imagery, and socio-political commentary construct particular perceptions of Muslim women’s veiling. The analysis reveals a tension between externally imposed stereotypes and self-articulated religious identities. The study argues that discursive practices on veiling simultaneously empower and constrain women, shaping public opinion, policy debates, and social norms. By critically engaging with both global and local texts, this research contributes to scholarship on Islamic feminism, media representation, and the politics of visibility, highlighting the need for nuanced understandings of agency, autonomy, and religio-cultural identity.